STUDY LAYANAN AIR MINUM PDAM BAGI MASYARAKAT MISKIN KOTA PALU - Nirmalawati, Nirmalawati; Tilaar, T A.M. (MEKTEK, 2005)
Water supply system provided by Perusahaan Daerah Air Minum (PDAM) plays an important role in fulfilling local citizen’s needs, both upper-middle and low classes of the society. Basically, water supply system involves three stakeholders: the users (the customers), the management (the company), and local government as a regulator. As a user, customer’s main concerns is the fulfillment of his/her needs with affordable price, whilst PDAM as the management aims to gain profit. In the other hand, local government aims to keep the balance between supply and demand while seeking growth in its income.Currently, water supply service in Palu is only accessible for those from upper-middle class whilst the poor cannot access the service due to its high tariff. The issue of the need of equal access to the standardized water supply system, that at the same time is affordable for every citizen, consequently has emerged. Therefore, it is necessary to conduct a study using Ability To Pay (ATP) and Willingness To Pay (WTP) approaches, taking into account the society’s real expenses and water supply system’s existing tariff. In subsequent, the subsidy for low-class society can be calculated.The population of this research consist of 408 households, spread into four districts. The primary data was collected by administering questionnaire using simple random sampling. Interviews were also conducted in order to gain more insight into the data. Secondary data was collected from PDAM Donggala and some other institutions. The data was analyzed using two techniques; first, ATP technique with household’s expenses approach; and second, WTP technique by taking user’s (customer) perception into consideration. The results showed that 75% of those who allocating 5% of their income to pay the PDAM’s bills had the ability to pay more than the tariff, whilst only 40% of those who allocating 3% of their income had the ability to pay more than the tariff. It is also appeared that none of the respondents were willing to pay more than the tariff (which is Rp.1450/m3). Further analysis showed that 47,3% of PDAM’s customers were able to subsidize to the poor, as their ability to pay (ATP) were mosre than Rp. 1500/m3